Saving the Face of Punjab Police: Learning from the Complexities of Zainab Case of Kasur - Ahmed, Muhammad Idrees (Journal of Pakistan Administration, 2022)
Kasur is the 24th largest district of Pakistan in terms of population and is spread over 3,995 square kilometers. It is located 55 Km. south of Lahore and is part of Sheikhupura Police Region (called a Range) of Punjab province. The 6th National census was held in Kasur district in April, 2017 during which the population was recorded at 3.46 million, with 25% being urban.2 There are four sub-divisions and 19 Police Stations (PS) in the district.